Comparison of Retzius-Sparing Robot-Assisted Radical Prostatectomy vs. Conventional Robot-Assisted Radical Prostatectomy: An Up-to-Date Meta-Analysis - Xu, Jiang-Nan; Xu, Zhen-Yu; Yin, Hu-Ming (Frontiers in Surgery, 2021)
Background: The Retzius Space Sparing Robot Assisted Radical Prostatectomy (RS-RARP) has shown better results in urinary continence, but its efficacy and safety compared to conventional RARP remains controversial. Material and Methods: A research was conducted in Medline via PubMed, Cochrane Library, EMBASE and Web of Science up to January 4, 2021 to identify studies comparing RS-RARP to c-RARP. We used RevMan5.3 and STATA 14.0 for meta-analysis. Results: A total of 14 studies involving 3129 participants were included. Meta-analysis showed no significant difference in positive surgical margins (PSM), but RS-RARP group had significantly higher PSM rates in the anterior site (OR=2.25, 95%CI 1.22 to 4.16, P=0.01). Postoperative continence in RS-RARP group at 1 month(OR=5.72, 95%CI 3.56 to 9.19, P<0.01), 3 months (OR=6.44, 95%CI 4.50 to 9.22, P<0.01), 6 months (OR=8.68, 95%CI 4.01 to 18.82, P<0.01) and 12 months (OR=2.37, 95%CI 1.20 to 4.70, P=0.01) was significantly better than that in c-RARP group. In addition, RS-RARP group had a shorter console time (MD=-16.28, 95%CI -27.04 to -5.53 P=0.003) and a lower incidence of hernia (OR=0.35, 95%CI 0.19 to 0.67, P=0.001). However, there were no significant differences in estimated blood loss, pelvic lymph node dissection rate, postoperative complications, 1-year-biochemical recurrence rate and postoperative sexual function. Conclusions: Compared with c-RARP, RS-RARP showed better recovery of continence, shorter console time, lower incidence of hernia. Although there was no significant difference in overall PSM, we suggest that the surgeon should be more careful if the lesion is in anterior prostate.